ENFORCe: A System for Ensuring Formal Correctness of High-level Programs - Azab, Karl; Habel, Annegret; Pennemann, Karl-Heinz; Zuckschwerdt, Christian (Electronic Communications of the EASST, 2007)
Graph programs allow a visual description of programs on graphs and graph-like structures. The correctness of a graph program with respect to a pre- and a postcondition can be shown in a classical way by constructing a weakest precondition of the program relative to the postcondition and checking whether the precondition implies the weakest precondition. ENFORCe is a currently developed system for ensuring formal correctness of graph programs and, more general, high-level programs by computing weakest preconditions of these programs. In this paper, we outline the features of the system and present its software framework.